Antioxidant Activities of RoJa Herbal Tea: Combination of Rosella Flower (Hibiscus sabdariffa L.) and Ginger Rhizome (Zingiber officinale Rosc.) - Widowati, Wahyu; Wargasetia, Teresa Liliana; Zakaria, Teddy Marcus; Gunadi, Michael Sebastian; Halim, Nathanael; Santiadi, Sherly; Kusuma, Hanna Sari Widya; Fauziyah, Nida Firyal (UI Scholars Hub, 2023)
Herbal teas and plant-based medicines have been widely used worldwide for their therapeutic and healing qualities. Rosella (Hibiscus sabdariffa L.) has various benefits in preventing digestive problems, liver disease, fever, and others. Ginger (Zingiber officinale Rosc.) or known as jahe in Indonesia is believed to benefit numerous clinical conditions linked to oxidative stress, including pancreatitis, hypertension, diabetic kidney disease, Alzheimer’s disease, and tumor development. They have been utilized in traditional medical practice to treat conditions such as fever, nausea, and headaches. In this study, we aimed to determine the antioxidant activities of rosella flower tea, ginger tea, and a combination of both, namely RoJa (Rosella-Jahe) tea. Antioxidant activities were analyzed by the 2,2-diphenyl-1-picrylhydrazyl (DPPH), hydrogen peroxide (H2O2), 2-2′-Azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) scavenging activities, and Ferric Reducing Antioxidant Power (FRAP) assay, as well as by measuring the amount of total phenolic and flavonoid content. Rosella tea had the greatest activity in the DPPH assay, with an IC50 value of 0.412 mg/ml. Ginger tea had the greatest activity for the ABTS, FRAP, and H2O2 tests, with IC50 values of 12.595 mg/ml, 0.494 mg/ml, and 1.323 mg/ml, respectively. Ginger tea also had the highest amount of total phenolic (3.61 µg GAE/g sample) and flavonoid content (11.81 µg QE/g). In conclusion, ginger tea showed the highest antioxidant activities, as well as total phenolic and flavonoid content, compared to rosella and RoJa tea.